Mindfulness‐based cognitive therapy for patients with chronic, treatment‐resistant depression: A pragmatic randomized controlled trial. Issue 10 (8th August 2018) - Cladder‐Micus, Mira B.; Speckens, Anne E.M.; Vrijsen, Janna N.; T. Donders, A. Rogier; Becker, Eni S.; Spijker, Jan
Abstract : Background: Chronic and treatment‐resistant depressions pose serious problems in mental health care. Mindfulness‐based cognitive therapy (MBCT) is an effective treatment for remitted and currently depressed patients. It is, however, unknown whether MBCT is effective for chronic, treatment‐resistant depressed patients. Method: A pragmatic, multicenter, randomized‐controlled trial was conducted comparing treatment‐as‐usual (TAU) with MBCT + TAU in 106 chronically depressed outpatients who previously received pharmacotherapy (≥4 weeks) and psychological treatment (≥10 sessions). Results: Based on the intention‐to‐treat (ITT) analysis, participants in the MBCT + TAU condition did not have significantly fewer depressive symptoms than those in the TAU condition (–3.23 [–6.99 to 0.54], d  = 0.35, P  = 0.09) at posttreatment. However, compared to TAU, the MBCT + TAU group reported significantly higher remission rates ( χ 2 (2) = 4.25, φ  = 0.22, P  = 0.04), lower levels of rumination (–3.85 [–7.55 to –0.15], d  = 0.39, P  = 0.04), a higher quality of life (4.42 [0.03–8.81], d  = 0.42, P  = 0.048), more mindfulness skills (11.25 [6.09–16.40], d  = 0.73, P  < 0.001), and more self‐compassion (2.91 [1.17–4.65], d  = 0.64, P  = 0.001). The percentage of non‐completers in the MBCT + TAU condition was relatively high ( n  = 12, 24.5%). Per‐protocol analyses revealed that those who completed MBCT + TAU had significantly fewer depressive symptoms at posttreatment compared to participants receiving TAU (–4.24 [–8.38 to –0.11], d  = 0.45, P  = 0.04). Conclusion: Although the ITT analysis did not reveal a significant reduction in depressive symptoms of MBCT + TAU over TAU, MBCT + TAU seems to have beneficial effects for chronic, treatment‐resistant depressed patients in terms of remission rates, rumination, quality of life, mindfulness skills, and self‐compassion. Additionally, patients who completed MBCT showed significant reductions in depressive symptoms. Reasons for non‐completion should be further investigated.